DI BALIK LIRIK CINTA: KAJIAN LEKSIKAL DAN GRAMATIKAL PADA LAGU SEAMIN TAK SEIMAN KARYA PETRUS MAHENDRA - Ramadhani, Tia; Ermawati; Andres Ita, Lila; Sulastri, Saptiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the lexical and grammatical meanings found in the lyrics of the song “Seamin Tak Seiman” by Petrus Mahendra. This song was chosen because of its powerful emotional message regarding differences in religious beliefs within romantic relationships, making it an interesting subject for linguistic analysis. The research method employed is qualitative descriptive, utilizing content analysis of the song lyrics as the primary focus of the study. The results indicate that the lexical meanings in this song are dominated by words expressing emotions—such as sadness, doubt, and hope—which align directly with dictionary definitions. Meanwhile, grammatical meaning emerges through word formation processes, the application of affixes, and the relationships between words in sentences, which enhance the overall meaning of the lyrics. Additionally, it was found that the use of simple yet poetic sentence structures effectively conveys the character’s inner conflict. Thus, this study demonstrates that the combination of lexical and grammatical meaning in song lyrics plays a crucial role in creating depth of meaning and a strong emotional impact for listeners.